2022
DOI: 10.3176/oil.2022.1.04
|View full text |Cite
|
Sign up to set email alerts
|

Effect of processing conditions on the improvement of properties and recovering yield of Moroccan oil shale

Abstract: In the present work, Moroccon Tarfaya oil shale was treated by acids and different solvents under supercritical conditions, successively. Experimental results showed clearly that residual mineral matter had a significant effect on the yield and composition of the resulting organic fraction. Indeed, the oil yields obtained from some samples, 43% and 56%, respectively, were much higher than that from the sub-layer, 18%. In addition, the yield of recuperation and quality of extracted oils were largely dependent o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…• Sample 3: sub-layer R 3 without carbonates and silicates → K 3 . The results of study of the effect of mineral matter on the recovery yield and composition of the extracted oils have been published recently [30]. These results showed that the yield of recuperation varies considerably among the different samples.…”
Section: Effect Of Mineral Matter On the Recovery Yield Of The Obtain...mentioning
confidence: 97%
See 1 more Smart Citation
“…• Sample 3: sub-layer R 3 without carbonates and silicates → K 3 . The results of study of the effect of mineral matter on the recovery yield and composition of the extracted oils have been published recently [30]. These results showed that the yield of recuperation varies considerably among the different samples.…”
Section: Effect Of Mineral Matter On the Recovery Yield Of The Obtain...mentioning
confidence: 97%
“…According to the previous work by Abourriche et al [30], the RH sample has several advantages, both in terms of preparation (less consumed products), and the results obtained (high recovery yield).…”
Section: Effect Of Mineral Matter On the Recovery Yield Of The Obtain...mentioning
confidence: 99%
“…An increase in the amount of hydrocarbon gases has a positive effect on the quality of the resulting product. 68.6% of the products was extracted by SWG from Moroccan Tarfaya oil shale at a temperature of 390 °C and an extraction time of 150 minutes [96]. Chham et al [97] used different solvents and wastewater from the olive oil production plant under sub-and supercritical conditions.…”
Section: Extraction From Oil Shalementioning
confidence: 99%
“…In addition to using water as a solvent, several studies have employed CO 2 , aromatic solvents (such as benzene, toluene) and ethanol for extraction [96,97,101,102]. CO 2 as a cheap solvent is very interesting in supercritical extraction, and the main efforts of researchers in recent years have been directed at studying the wettability effect of coal and oil shale.…”
Section: Extraction From Oil Shalementioning
confidence: 99%
“…The valorization of these resources can provide a significant and highly interesting objective. In recent years, several research studies have focused on developing new materials for various applications using these resources [1] [2] [3] [4] [5].…”
Section: Introductionmentioning
confidence: 99%